THE ROLE OF NON-TRADITIONAL DAIRY PRODUCTS IN THE DIET OF THE POPULATION OF KARAKALPAKSTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article describes the solution of the problems that have arisen in connection with the tense environmental situation in the southern Aral Sea region. To do this, it is necessary to make an effort to widely develop and use environmentally friendly products from local livestock raw materials. In connection with the current situation, in order to increase the immunity of the population, non-traditional dairy products should be used in everyday life. In this case, the article provides a comparative physical and chemical analysis of cow and camel milk. Studies show that camel milk has been studied quite well by scientists in a number of countries and introduced into production.